Prevalencia de candida albicans en cavidad oral de personas sistemicamente sanas. Revisión de la literatura (2020)
Candida is an opportunistic yeast that usually colonizes mucous membranes of the skin, gastrointestinal and genitourinary tract. C. albicans is part of the normal microbiota in the oral cavity but has the ability to become pathogenic in favorable states, inducing Candidiasis. Objective: To determine the prevalence of Candida albicans in the oral cavity of systemically healthy patients according to what is reported in the literature. Materials and Methods: A systematic literature review was carried out to identify publications related to the prevalence of Candida albicans in healthy subjects, articles guided by title and abstract were selected until full texts were obtained, information search was performed in: Medline, PubMed, SciELO., Latindex, obtaining 45 articles related to the subject of which 11 reported the frequency of Candida spp, in healthy subjects, with publication dates between the years 2010-2019. Results: The presence of Candida spp. in 573 healthy subjects 34.35% of the patients. A total of 420 of 1,663 subjects presented C. albicans with 25.25% and corresponded to the highest number of isolates, followed by C. glabrata with 3.36%. A statistically significant correlation was found between orthodontic appliances (p <0.001), use of dental prostheses (p <0.001) and smoking (p <0.05) with Candida colonization. Conclusion: The prevalence of C. albicans in the oral cavity of healthy subjects was 25.25%, there being colonization by non-albicans species in 9.2%, among the possible factors associated with colonization by Candida, the use of prostheses is reported dental, orthodontic treatment and smoking.